2019
DOI: 10.14740/wjon1230
|View full text |Cite
|
Sign up to set email alerts
|

Combining Prostate-Specific Antigen Parameters With Prostate Imaging Reporting and Data System Score Version 2.0 to Improve Its Diagnostic Accuracy

Abstract: BackgroundAny non-invasive test that can predict the absence of prostate cancer (PCa) or absence of clinically significant PCa (CSPCa) is necessary, as it can reduce the number of unnecessary biopsies in patients with gray zone prostate-specific antigen (PSA, 4 - 10 ng/mL). This study evaluated the diagnostic performance of free PSA% and PSA density (PSAD), and Prostate Imaging Reporting and Data System (PIRADS) score (version 2.0) alone and combined in predicting CSPCa in patients with PSA between 4 and 10 ng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Jordan et al also support the use of PSA density, noting that PI-RADS v2 + PSAD is better than PI-RADSv2 alone [19]. Similar findings have been proposed by Schoots et al in active surveillance population, by Baruah et al, and by Maggi et al who conducted a meta-analysis, although a threshold of 0.15 ng/ml/ml was used [24,[31][32]. There is also evidence that points to combining the 4K-score test or the European Randomized Study of Screening for Prostate Cancer risk calculator (ERSPC-RC) with mpMRI to better identify clinically significant disease [33].…”
Section: Discussionsupporting
confidence: 55%
“…Jordan et al also support the use of PSA density, noting that PI-RADS v2 + PSAD is better than PI-RADSv2 alone [19]. Similar findings have been proposed by Schoots et al in active surveillance population, by Baruah et al, and by Maggi et al who conducted a meta-analysis, although a threshold of 0.15 ng/ml/ml was used [24,[31][32]. There is also evidence that points to combining the 4K-score test or the European Randomized Study of Screening for Prostate Cancer risk calculator (ERSPC-RC) with mpMRI to better identify clinically significant disease [33].…”
Section: Discussionsupporting
confidence: 55%
“…1 The Prostate Imaging-Reporting and Data System (PI-RADS) has standardised the diagnosis of prostate cancer using MRI and is effective for characterisation of prostate cancer. 2 However, MRI is still restricted by benign confounding appearances and substantial intra-reader and inter-reader variability. 3 Therefore, Gleason grade grouping (GGG), which assigns a prostate cancer lesion to one of five categories (1āˆ’5) based on invasive biopsies, remains the standard of care in determining the aggressiveness of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, the Prostate Imaging-Reporting and Data System (PI-RADS) was released to improve the reporting standardization of mpMRI. 5 Patients who had positive results on the mpMRI were suggested to undergo MRI targeted biopsy through real-time ultrasonographic guidance. 6 Multiple previous studies have proved that prostate biopsy procedures with needles targeted at MRI-identified lesions could improve the cancer detection rate and quantity of cancer per biopsy core when compared with systematic 12-core biopsy.…”
Section: Introductionmentioning
confidence: 99%